Analysis of Factors Affecting the Profitability of Bank Syariah Indonesia (BSI) - Nurul Innayah; Abdul Aziz; Diana Djuwita (Mutanaqishah: Journal of Islamic Banking, 2023)
This study aims to analyze the effect of Non-Performing Financing, Operating Costs, Operating Income, Capital Adequacy Ratio and Financing to Deposit Ratio partially or simultaneously on Profitability as measured by Return on Assets at Sharia Commercial Banks. The population of this study is Sharia Commercial Banks listed on the Indonesia Stock Exchange. The research data is quantitative data obtained from the quarterly financial statements for the 2021-2022 period. The data analysis method of this research is regression analysis of panel data using EViews 12 software. The results of this study show that independent variables namely NPF, BOPO, CAR and FDR simultaneously affect ROA with a significance value of F below 5%. Partially, independent variables (NPF, BOPO, CAR and FDR) have a negative and significant effect on ROA, because all independent variables have significant values below 5%. The value of the coefficient of determination (R2) is 0.967. This shows that 96% of each change in ROA can be explained by NPF, BOPO, CAR and FDR variables, the remaining 4% is influenced by other factors not explained in this study.